Scientific Achievements and legacy of Professor Eduardo Couve Montané: A narrative review. - Suzuki Barrera, Kiyoko (Applied Sciences in Dentistry, 2022)
Reviewing the history and achievements of professors can teach and inspire the next generation to pursue their research and legacy. For this reason, the present paper reviews the scientific achievements and legacy of Professor Eduardo Couve. Professor Eduardo Couve developed an outstanding academic career in the University of Valparaíso. In his research he merged his knowledge in cell and oral biology with his accurate management of microscopy, especially electron and confocal microscopes. This allowed him to develop interesting and diverse papers. Through all his research it is possible to observe a logical and consistent cycle of evidence production influenced by advances in microscopy and collaborations. The conceptualization of the pulp as a sensory organ and a multicellular barrier from an evolutionary perspective, shows a thorough analysis and reflective process of the available evidence and the influence of the different areas of knowledge for a better understanding of dental pulp and tooth. The real impact of his influence on the countless generations he taught and on all the colleagues he worked with and enjoyed collaborations with, may never be measured, but surely the influence of his career and research will be present for a long time in the development of dental research both in Chile and abroad.